Mending the broken link: heterogeneous bank lending and monetary policy pass-through - Carlo Altavilla; Fabio Canova; Matteo Ciccarelli (European Central Bank (ECB), 2016)
We analyse the pass-through of monetary policy measures to lending rates to firms and households in the euro area using a unique bank-level dataset. Bank balance sheet characteristics such as the capital ratio and the exposure to sovereign debt are responsible for the heterogeneity of pass-through of conventional monetary policy changes. The location of a bank is instead irrelevant. Non-standard measures normalized the capacity of banks to grant loans resulting in a significant compression in lending rates. Banks with a high level of non-performing loans and a low capital ratio were the most responsive to the measures. Finally, we quantify the effects of non-standard policies on the real economic activity using a standard macroeconomic model and find that in absence of these measures both inflation and output would have been significantly lower.
Keywords: C3; E4; E5; G2; 330; bank balance sheet characteristics; monetary policy pass-through